Association between high levels of inflammatory markers and cognitive outcomes at 4 years of age: The Rhea mother-child cohort study, Crete, Greece. (May 2019) - Kyriklaki, Andriani; Margetaki, Katerina; Kampouri, Mariza; Koutra, Katerina; Bitsios, Panos; Chalkiadaki, Georgia; Dermitzaki, Eirini; Venihaki, Maria; Sarri, Katerina; Anousaki, Despoina; Kogevinas, Manolis; Chatzi, Leda
Highlights: We found inverse associations of high TNF-α concentrations with three memory scales. High IFN-γ levels were related to lower scores in memory span at preschool age. Elevated TNF-α/IL-10 ratio was associated with decreased scores in various scales. High levels of TNF-α may contribute to reduced memory performance at preschool age. Abstract: There is growing evidence associating inflammatory markers in complex, higher order neurological functions, such as cognition and memory. We examined whether high levels of various inflammatory markers are associated with cognitive outcomes at 4 years of age in a mother-child cohort in Crete, Greece (Rhea study). We included 642 children in this cross-sectional study. Levels of several inflammatory markers (IFN-γ, IL-1β, IL-6, IL-8, IL-17α, IL-10, MIP-1α, TNF-α and the ratios of IL-6 to IL-10 and TNF-α to IL-10) were determined in child serum via immunoassay. Neurodevelopment at 4 years was assessed by means of the McCarthy Scales of Children's Abilities. Multivariate linear regression analyses were used to estimate the associations between the exposures and outcomes of interest after adjustment for various confounders. Our results indicate that children with high TNF-α concentrations (≥90 th percentile) in serum demonstrated decreased scores in memory (adjusted β = −4.0; 95% CI: −7.7, −0.2), working memory (adjusted β = −4.0; 95% CI: −8.0, −0.1) as well as in memory span scale (adjusted β = −4.0; 95% CI: −7.9, −0.1). We also found that children with high IFN-γ serum levels showed lower scores in memory span scale (adjusted β = −3.4; 95% CI: −7.3, −0.4). Children with elevated TNF-α/IL-10 ratio demonstrated decreased quantitative (adjusted β = −4.3; 95% CI: −8.2, −0.4), motor (adjusted β = −3.5; 95% CI: −7.5, −0.5), executive function (adjusted β = −4.8; 95% CI: −8.5, −1.1), general cognitive (adjusted β = −3.6; 95% CI: −7.3, −0.1), memory (adjusted β = −3.8; 95% CI: −7.6, −0), working memory (adjusted β = −3.5; 95% CI: −7.5, −0.5) and memory span scores (adjusted β = −5.3; 95% CI: −9.1, −1.4) The findings suggest that high levels of TNF-α may contribute to reduced memory performance at preschool age.